2022
DOI: 10.3389/fmolb.2022.915409
|View full text |Cite
|
Sign up to set email alerts
|

TRPs in Ovarian Serous Cystadenocarcinoma: The Expression Patterns, Prognostic Roles, and Potential Therapeutic Targets

Abstract: Ovarian cancer (usually ovarian serous cystadenocarcinoma, or OV) is the fifth leading cause of cancer-related deaths in women, with more than 184,000 deaths reported worldwide annually, and is a highly malignant carcinoma. However, the mechanism of etiology remains unclear. The lack of prognostic and diagnostic biomarkers is a main limitation for clinical diagnosis and treatment. The transient receptor potential (TRP) channels play essential roles in the occurrence and development of cancers which may have th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, patients with OC who express higher levels of TRPV4 may be more resistant to the chemotherapeutic drugs cisplatin and oxaliplatin. Zhang et al (42) previously reported that screened high TRPV4 expression was associated with poor prognosis in patients with ovarian serous cystadenocarcinoma and also demonstrated by Cox regression analysis that TRPV4 was the most probable therapeutic target for ovarian serous cystadenocarcinoma. The role of TRPV4 in the dysregulation of cell migration and adhesion may be crucial for the poor prognosis in OC.…”
Section: Plasma Membrane Ca 2+ Channelsmentioning
confidence: 90%
“…Furthermore, patients with OC who express higher levels of TRPV4 may be more resistant to the chemotherapeutic drugs cisplatin and oxaliplatin. Zhang et al (42) previously reported that screened high TRPV4 expression was associated with poor prognosis in patients with ovarian serous cystadenocarcinoma and also demonstrated by Cox regression analysis that TRPV4 was the most probable therapeutic target for ovarian serous cystadenocarcinoma. The role of TRPV4 in the dysregulation of cell migration and adhesion may be crucial for the poor prognosis in OC.…”
Section: Plasma Membrane Ca 2+ Channelsmentioning
confidence: 90%
“…Transient receptor potential (TRP) channels are important mediators of sensory perception with significant effects on cellular functions and signalling pathways. Based on sequence homology, the mammalian TRP channel superfamily is classified the majority of TRPs are more selective for calcium, which is considered the most important second messenger involved in physiology and pathological events, such as cancer progression ( Morelli and Amantini, 2022 ; Zhang et al, 2022 ). Transient receptor potential melastatin 4 (TRPM4) channel is a Ca 2+ -activated nonselective cation channel, belonging to the TRPM family of TRP channels, highly selective for monovalent cations such as Na + and K + , but impermeable to anions and divalent cations including Ca 2+ ( Launay et al, 2002 ; Guo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%